Early application of cryoanalgesia to the brachial plexus prevents development of phantom limb pain after traumatic forequarter amputation: A case report - Lizabeth A. O'Connor; Bryan Houseman; Daniel Taffe; Curtis C. Quinn (Trauma Case Reports, 2022)
Background: Amputation of an extremity frequently results in significant phantom limb pain. The etiology of which is not well understood. Central and peripheral factors appear to play a role. Pain relief interventions often are attempted several weeks to months later. Peripheral nerve injury can rapidly result in cortical somatosensory changes potentially making early intervention important in preventing any permanent changes in nerve pathways. Case report: We present a case of traumatic forequarter (interscapulothoracic) amputation treated with cryoanalgesia of the brachial plexus for pain control <72 h after injury. The patient denied painful phantom limb pain and postoperative pain at the surgical site immediately following surgery and over a six month follow up period. Conclusion: Cryoanalgesia facilitates extended duration of pain control of the affected peripheral nerve which may be of particular benefit in patients sustaining either surgical or traumatic amputations, particularly when applied early to prevent the transmission of noxious signals to the central nervous system.